Missing daughters? A 6-year village-level study of sex ratio trends at birth and its correlation with MTP and abortion in central India - Nimje, Ashish T.; Padole, Wandana H. (International Journal Of Community Medicine And Public Health, 2025)
Background: India has experienced persistent gender imbalances, with declining sex ratios at birth (SRB) largely attributed to son preference, sex-selective abortions, and the misuse of reproductive technologies. Despite legislative measures such as the PCPNDT Act, skewed SRBs remain prevalent, especially in rural regions. While national-level data highlight this trend, there is a dearth of village-level, time-bound analyses examining the role of Medical Termination of Pregnancy (MTP) in influencing SRB. This study aims to analyze village-wise SRB trends over six years in a Central Indian block and assess their correlation with MTP and abortion data, particularly among women with previous female children. Methods: A retrospective observational study was conducted using secondary data from 2019 to 2025, sourced from sub-centres, PHCs, CHCs, and private facilities. Data included annual live births disaggregated by sex and MTP/abortion cases categorized by maternal parity. Villages were anonymized, and statistical analyses, including Spearman’s correlation, were performed to explore associations between SRB and MTP/abortion trends. Results: SRB varied significantly across villages, with values ranging from as low as 720 to over 1200 across years. Abortions and MTPs were consistently higher among women with one or more daughters, with a peak in 2024-25. However, Spearman’s correlation revealed only a moderate, statistically insignificant relationship between SRB and MTP (rs=0.4857, p=0.3287), and a negligible correlation with abortions (rs=0.0857, p=0.8717). Conclusions: The findings suggest that gender preference may subtly influence abortion patterns, even if not strongly reflected in statistical correlation. Persistent low SRBs in certain villages signal the need for targeted, grassroots-level interventions to combat sex-selective practices and promote gender equity.